226k views
2 votes
8. 6 - 4x = 6x - 8x + 2

X=

User SenG
by
6.0k points

1 Answer

3 votes

Answer:

x =2

Explanation:

Solve for x:

6 - 4 x = 2 - 2 x

Add 2 x to both sides:

2 x - 4 x + 6 = (2 x - 2 x) + 2

2 x - 2 x = 0:

2 x - 4 x + 6 = 2

2 x - 4 x = -2 x:

-2 x + 6 = 2

Subtract 6 from both sides:

(6 - 6) - 2 x = 2 - 6

6 - 6 = 0:

-2 x = 2 - 6

2 - 6 = -4:

-2 x = -4

Divide both sides of -2 x = -4 by -2:

(-2 x)/(-2) = (-4)/(-2)

(-2)/(-2) = 1:

x = (-4)/(-2)

The gcd of -4 and -2 is -2, so (-4)/(-2) = (-2×2)/(-2×1) = (-2)/(-2)×2 = 2:

Answer: x = 2

User UmeshR
by
4.9k points